2004
DOI: 10.1093/annonc/mdh395
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel and epirubicin versus paclitaxel and carboplatin as first-line chemotherapy in patients with advanced breast cancer: a phase III study conducted by the Hellenic Cooperative Oncology Group

Abstract: Our study suggests that the paclitaxel/Cp combination is an effective therapeutic alternative for patients with ABC in which anthracycline administration has the potential of being harmful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 22 publications
1
31
1
Order By: Relevance
“…The latter however, needs to be viewed with caution, since subgroup analyses are usually underpowered and exploratory and are mainly hypothesis generating. Survival rates at two-years ranged from 56% for GDoc, 61% for PCb to 67% for Pw, higher than the observed survival rates in the previous randomized study by our group [10], in which the corresponding 2-year survival rates were 45% and 53% for the paclitaxel/epirubicin and PCb groups, respectively. This improvement in all treatment arms could probably be attributed to the wider use of trastuzumab and the availability of additional effective chemotherapy agents in subsequent lines of treatment such as capecitabine for patients in the current study.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The latter however, needs to be viewed with caution, since subgroup analyses are usually underpowered and exploratory and are mainly hypothesis generating. Survival rates at two-years ranged from 56% for GDoc, 61% for PCb to 67% for Pw, higher than the observed survival rates in the previous randomized study by our group [10], in which the corresponding 2-year survival rates were 45% and 53% for the paclitaxel/epirubicin and PCb groups, respectively. This improvement in all treatment arms could probably be attributed to the wider use of trastuzumab and the availability of additional effective chemotherapy agents in subsequent lines of treatment such as capecitabine for patients in the current study.…”
Section: Discussioncontrasting
confidence: 75%
“…Three of them, paclitaxel and carboplatin [3,4], docetaxel and gemcitabine [5,6] and weekly paclitaxel [7][8][9] have demonstrated significant activity and manageable toxicity. Furthermore, the first of these combinations was found to be effective in a phase III trial [10], when compared to the combination of paclitaxel and epirubicin, in terms of overall response rate (ORR), survival and quality of life (QoL).…”
Section: Introductionmentioning
confidence: 99%
“…These patients participated in ten trials designed and run consecutively by HeCOG, exploring different first-line treatment options for patients with MBC [8][9][10][11][12][13][14][15][16][17]. Information was collected prospectively according to the corresponding trial protocol and deposited in the central HeCOG office database.…”
Section: Methodsmentioning
confidence: 99%
“…In a phase III study, the combination of paclitaxel and carboplatin showed no significant difference in survival as compared with paclitaxel and epirubicin; however, only 25% of patients in that study had received adjuvant anthracyclines [42]. Thus, the level of recommendation of such a combination for this subgroup of patients remains low (level of evidence IbB).…”
Section: Taxanes Combined With Other Cytotoxic Drugsmentioning
confidence: 97%